ANALISIS PELAKSANAAN ELECTRONIC GOVERMENT PADA KANTOR PENGAWASAN & PELAYANAN BEA CUKAI TIPE PRATAMA TEGAL - Yogi Arif Ramdhanu; Kushandajani .; Puji Astuti (Journal of Politic and Government Studies, 2016)
In this globalization era, information becomes an important commodity. As the growth of technology development, people want a fast, easy and efficient service. In the case of the high requirement towards the enhancement of public service quality, Directorate General of Customs and Excise becomes one of the government institutions which does the transformation by applying information technology based service and integrated communication. Problem formulation on this research is “How is the implementation of electronic government in the environment of Kantor Pengawasan & Pelayanan Bea Cukai (KPPBC) Type of Pratama Tegal?” and “What are the outcomes or results from government electronic system that have been implemented by KPPBC Type of Pratama Tegal?”. This research is aimed to explain about the implementation of electronic government and find out about the outcomes or results from the electronic government system that have been implemented by KPPBC Type of Pratama Tegal. The research method that have been used in this research is qualitative by using data collecting method that is interview with research object, observation and based on secondary data which is available and earned. The results of this research shows that the implementation of electronic government in KPPBC Type of Pratama Tegal based on the implementation theory of George Edward III have gone pretty well with some errors, for instance the lack of human resources quantity and quality from internet connectivity, as well as the disturbance on server which causes downtime system can find the outcomes from the implementation of electronic government in KPPBC Type of Pratama Tegal, that becomes faster and easier service, to increase efficiency for the service user, to increase transparency and to prevent the existence of corruption, as well as to ease the supervision. The recommendations that can be given are; to maximize the supervision and service in KPPBC Type of Pratama Tegal need to increase capacity from server and increase internet speed, besides the existence of reserve connection by using another operator if there is disturbance on the operator that is now being used. Keywords: Analysis, implementation, electronic government, KPPBC Type of Pratama